Contractual Obligations in Financing with Fiduciary Security in Indonesia in the Context of Justice - T. Muhammad Ali Bahar; Tan Kamello; Suhaidi Suhadi; Saidin Saidin; Rio Hilmawan Bagas Trihasworo (Universitas Negeri Semarang, 2023)
Financing with fiduciary security in Indonesia raises justice-related concerns. This study focuses on analyzing contractual obligations in this type of financing within the context of justice. It reveals several key issues. Firstly, an imbalance of power exists between creditors and debtors, with creditors holding a stronger position in executing fiduciary security. Secondly, consumer protection and debtor rights remain inadequate, leading to injustice for financially vulnerable debtors who struggle to fulfill their payment obligations. Thirdly, dispute resolution tends to favor creditors, resulting in lengthy legal proceedings and high costs that hinder debtors from achieving justice. Additionally, the lack of public understanding and awareness about their rights in financing with fiduciary security further exacerbates the problem. These factors collectively contribute to injustice in financing with fiduciary security and call for improvements in the system to ensure fair treatment for all parties involved.